Reflexões sobre o ensino de ciências nos 6º e 9º anos do ensino fundamental: novas perspectivas - FARIAS, Maria Valdemira dos Santos (2024)
This study aimed to analyze the methodologies and teaching resources, show the conception of the teacher in relation to the teaching of science and identify the reason that leads methodologies and teaching resources used. The data for the development of the research were collected in the State School of Elementary and Secondary Education Pedro Teixeira belonging to the municipality of Abaetetuba-PA. The methodology consisted primarily the literature on the history of Science Teaching at the school and the methodologies used in school. Then went to action research and field research by collecting data through a structured interview with two teachers, one of a group of year 6 and another of a class of 9 year / 9 school in focus. In the results, we identified the methodologies used (lectures and expository transcript content within magnetic resolutions exercises, workshops, experiments and field research), the resources used by teachers (magnetic board, textbooks, posters, computer and data-show), we show the design of the teacher in relation to science teaching (contextualize the issue and that the student understands the medium in lives) and identify the reasons why teachers resort to the methods used (lack of time to study and plan lessons, lack of teaching resources and do not participate in continuing education in the area). These results brought us confirmation that the methodological practice of the teacher exerts a strong influence on the learning process. With this information, educators can act more safely as they need theoretical basis to reflect on their teaching practice. Thus, this study sought to bring questions and reflections about the teaching of science from 6th to 9th grade. It also brought to these educators, the necessary foundation for understanding the process of teaching and learning of science, andrew perspectives.